Underlying Factors of Problematic Online Gaming Behavior: Age, Intensity, and Genre - Şendurur, Emine; Şendurur, Polat (Addicta: The Turkish Journal on Addictions, 2018)
Modern games offer rich user experiences through the inclusion of multimedia, increased mobile capabilities, high fidelity interfaces, and increased accessibility. Since games are integrated into a wide variety of environments, their effects on people’s lives may exhibit a myriad of difference and may sometimes lead to problems that project into real life. In this study, we attempted to understand the problematic online game use of a group of gamers by examining a series of psychological, physical, and demographical factors. We reached the participants through the help of a fan page on a popular social networking site, surveying them online and conducting interviews with volunteers. The results showed that age, game genre, and excessive playing had significant effects on problematic online game usage. Among all age categories, elementary school aged gamers reported higher frequencies of losing self-control while playing. Among all genres, gamers who prefer Massive Multiplayer Online Role-Playing Games were found to experience more problems related to euphoria and conflict. On the other hand, the gamers in this study were aware of the fact that they spent excessive amounts of time playing games as well as the negative effects that playing too much had on their real lives. These excessive gamers also reported conflicts, failure to control themselves, and health related problems. To